2018
DOI: 10.1093/gerona/gly026
|View full text |Cite
|
Sign up to set email alerts
|

Change in Cardiometabolic Risk Among Blacks, Whites, and Hispanics: Findings From the Health and Retirement Study

Abstract: We show that the cardiometabolic health of older blacks worsens as they age both absolutely and relative to that of whites and Hispanics because of poor blood pressure control and diabetes prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
(41 reference statements)
1
21
1
Order By: Relevance
“…Covariates. We controlled for participant and couple characteristics, including age, education, self-rated health, race/ ethnicity, marital strain, partnership status, marital duration, presence of coresident children, and subsample year (2008/ 2012 vs. 2010/2014) as these may all be associated with loneliness and physiological health (Das, 2019;Mitchell et al, 2019;O'Luanaigh et al, 2012;Stokes, 2017b;Tampubolon & Maharani, 2018). Age was measured as a continuous variable, in years.…”
Section: Predictors Of Interestmentioning
confidence: 99%
“…Covariates. We controlled for participant and couple characteristics, including age, education, self-rated health, race/ ethnicity, marital strain, partnership status, marital duration, presence of coresident children, and subsample year (2008/ 2012 vs. 2010/2014) as these may all be associated with loneliness and physiological health (Das, 2019;Mitchell et al, 2019;O'Luanaigh et al, 2012;Stokes, 2017b;Tampubolon & Maharani, 2018). Age was measured as a continuous variable, in years.…”
Section: Predictors Of Interestmentioning
confidence: 99%
“…This absence of a significant difference in risk is an unexpected finding because prior research has shown that Blacks have a greater average number of cardiovascular risk factors than Whites regardless of sex. 20,23,32,33 One possible explanation is that past efforts at reducing disparities in cardiovascular risk factors and improving the cardiovascular health of Black men have been successful. However, it is unlikely that disparities in cardiovascular risk would have been eliminated prior to the 1990s.…”
Section: Change In Cardiovascular Risk: 1990 -2010 -Mitchell Et Almentioning
confidence: 99%
“…Several studies have documented broad psychological distress or depression among older adults who face financial hardship ( 60 , 61 ). Older adults who have difficulty paying bills have been shown to delay or forego taking medications due to cost, which can have a devastating impact on mental health symptoms ( 62 , 63 ) in addition to their physical health ( 50 ). These findings suggest that experiencing financial or housing insecurity in older adulthood poses a threat to the mental health of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…First, measuring symptomology limits bias due to differential access to health care across respondents that can be introduced by only measuring diagnoses. Self-reports of diagnosed disorders that are often found in nationally representative samples may underestimate and misrepresent health for older black adults who have been historically excluded from the health care system and often distrust and have less access to health care that provides diagnoses ( 50 ). Second, symptomology measures generally have more variation than simple yes/no measures of diagnosis ( 51 ).…”
Section: Background and Objectivesmentioning
confidence: 99%